Herbicides for weed control in the root crops Ullucus tuberosus and Amorphophallus konjac - James, T.K.; Follett, J.M. (New Zealand Plant Protection, 2000)
Ullucus tuberosus and Amorphophallus konjac are new root crops being evaluated for commercial development in New Zealand Eighteen herbicides were screened in glasshouse experiments for pre or postemergence use in these crops Methabenzthiazuron chlorpropham diuron and linuron were well tolerated by Ullucus when applied preemergence while dimethanamid oryzalin and simazine warrant further study All the postemergence treatments damaged Ullucus although linuron might show acceptable tolerance at a lower rate Acetochlor chlopropham dimethanamid linuron methabenzthiazuron oryzalin oxadiazon oxyfluorfen and pendimethalin were all well tolerated by Amorphophallus when applied preemergence while asulam flumetsulam and tribenuron were safely used postemergence Bromoxynil was also safe on Amorphophallus if applied before leaves emerged from the developing shoot